Kendala Guru Dalam Pelaksanaan Penilaian Autentik pada Pembelajaran Geografi Di SMA Negeri Bandar Lampung - Dian Utami; Edi Haryono (SPATIAL: Wahana Komunikasi dan Informasi Geografi, 2021)
The purpose of this study was to (1) understand authentic reporting on geography learning at SMA Negeri Bandar Lampung. (2) examining what the teacher teaches in carrying out authentic geography subjects at SMA Negeri Bandar Lampung. This research method is to use a descriptive qualitative approach. Data collection using interviews and documentation. The population of this research is the geography teacher at SMA Negeri Bandar Lampung. The research sample was geography teachers from SMA N 9, SMA 14, SMA 15 in Bandar Lampung. The results of the teacher's research threw authentic instruments and outputs. But the instruments made are not very complete and not all indicators are in every aspect of value. In general, geographic errors.